2021
DOI: 10.1038/s41598-020-80256-7
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and seeding strategies for wheat optimizing production in harvested rice fields with high soil moisture

Abstract: Suitable tillage and seeding strategies for wheat can be used to combat excessive residues and poor soil conditions in harvested rice fields. This study investigated the effects of different tillage (zero tillage and rotary tillage) and seeding methods on wheat growth, grain yield, nitrogen (N) uptake and utilization, and economic benefit when the soil moisture was high during the tillage and seeding practices. In 2016–2017, three seeders were tested: SM1-1, SM2, and SM3; in 2017–2018, four seeders were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…A study conducted on various irrigation regimes on wheat in China concluded that the nitrogen partial factor productivity was higher for 40 mm per irrigation (41.57 to 43.69 kg grain per kg N applied) compared with 20 mm per irrigation (32.24 to 32.47 kg grain per kg N applied) ( Si et al., 2020 ). High crop growth rate, yield, and N uptake in crops can be achieved by maintaining optimal soil moisture conditions ( Giller et al., 2004 ; Ding et al., 2021 ). Annual crops have a higher agronomic NUE than perennial crops due to the higher N uptake efficiency and N concentration ( Weih et al., 2011 ).…”
Section: Factors Affecting Agronomic Nue Of Various Cropsmentioning
confidence: 99%
“…A study conducted on various irrigation regimes on wheat in China concluded that the nitrogen partial factor productivity was higher for 40 mm per irrigation (41.57 to 43.69 kg grain per kg N applied) compared with 20 mm per irrigation (32.24 to 32.47 kg grain per kg N applied) ( Si et al., 2020 ). High crop growth rate, yield, and N uptake in crops can be achieved by maintaining optimal soil moisture conditions ( Giller et al., 2004 ; Ding et al., 2021 ). Annual crops have a higher agronomic NUE than perennial crops due to the higher N uptake efficiency and N concentration ( Weih et al., 2011 ).…”
Section: Factors Affecting Agronomic Nue Of Various Cropsmentioning
confidence: 99%
“…In this study, the impact of heat stress on wheat yield, during anthesis and grain-lling stages evaluate the role of supplement irrigation in mitigating of heat stress. Some strategies such as rescheduling of sowing time, conservation agriculture and supplement irrigation to reduce the effect of terminal heat stress conditions on wheat farming (Birthal et al, 2021;Ding et al, 2021bDing et al, , 2021bDing et al, , 2021aSharma et al, 2022;Tamta et al, 2021;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Full tillage is conducive to breaking hardpan, mixing crop residues with soil to improve soil porosity, as it promotes the extension of the roots into the subsoil, which contributes to nutrient uptake and wheat yield improvement [1,[4][5][6][7]. In arid regions, however, loose soil leads to the rapid evaporation of soil moisture, negatively affecting water use and crop growth [8].…”
Section: Introductionmentioning
confidence: 99%
“…In arid regions, however, loose soil leads to the rapid evaporation of soil moisture, negatively affecting water use and crop growth [8]. Full tillage can easily result in deep sowing, which makes plants susceptible to high soil moisture, likely causing hypoxia stress [4,9]. No-tillage can stabilize soil structure to reduce water evaporation and improve drought resistance [10][11][12], but it increases the mechanical impediment of the surface soil, thereby limiting the root distribution in the upper soil profile and downward progression [13,14].…”
Section: Introductionmentioning
confidence: 99%